2019
DOI: 10.1002/ese3.598
|View full text |Cite
|
Sign up to set email alerts
|

Failure characteristics and control technology for large‐section chamber in compound coal seams—A case study in Tashan Coal Mine

Abstract: The coal production exploited from extra‐thick coal seams accounts for 45% of China's total coal production. With large coal output, the extra‐thick coal seams require that the chamber section be more than 100 m2. In case of parting (the noncoal rock, usually mudstone, sandwiched in the coal seam) in the extra‐thick coal seams, the integrity of the coal seams will be damaged and the large‐section chamber is extremely easy to occur rib spalling and roof leakage, which will increase the chamber's supporting diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…erefore, decreasing the pressure on the coal wall and increasing the shear strength and cohesion of the coal were the main methods for preventing the coal wall from spalling. However, no sensitivity or coal dip analyses were conducted in [34,37], while the findings in this study are corroborated by the above analyses.…”
Section: Shear Failure Mechanism Of the Coal Wall Elementsupporting
confidence: 46%
See 2 more Smart Citations
“…erefore, decreasing the pressure on the coal wall and increasing the shear strength and cohesion of the coal were the main methods for preventing the coal wall from spalling. However, no sensitivity or coal dip analyses were conducted in [34,37], while the findings in this study are corroborated by the above analyses.…”
Section: Shear Failure Mechanism Of the Coal Wall Elementsupporting
confidence: 46%
“…Nevertheless, the increment in the force from the equipment is limited, as is the element strength increment. Wang [34] and Tai et al [37] proposed a plane strain model of coal wall carving and reported that both tensile and shear failures were related to the roof pressure, shear strength, and characteristics of the coal. erefore, decreasing the pressure on the coal wall and increasing the shear strength and cohesion of the coal were the main methods for preventing the coal wall from spalling.…”
Section: Shear Failure Mechanism Of the Coal Wall Elementmentioning
confidence: 99%
See 1 more Smart Citation
“…These problems are all related to the deformation and damage of the overburdens caused by the mining of coal resources. Therefore, how to effectively predict the deformation and cracking of the overburdens of the mining coal seams has a very important practical significance for the protection of the overlying aquifers and surface water resources and the prediction of mine water damage accidents [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The roof of a compound roof roadway is prone to abscission and subsidence, while both sides are loose coal, therefore, under the pressure of the overlying strata, the interaction between the compound roof and the two sides makes the condition of the surrounding rock worsen, which will lead to instability and even the collapse of the roadway. According to incomplete statistics, over 30% of coal layer roadways in China have compound roofs and this percentage is increasing with the increase of mining depth [7][8][9][10]. The maintenance of roadways with compound roofs has become a choke point for mines in China to extend to deeper areas.…”
Section: Introductionmentioning
confidence: 99%